Multifaceted impacts of nanoparticles on plant nutrient absorption and soil microbial communities - Zhang, Hanfeng; Zheng, Tiantian; Wang, Yue; Li, Ting; Chi, Qing (Frontiers in Plant Science, 2024)
With the growth of the global population and the increasing scarcity of resources, the sustainability and efficiency improvement of agricultural production have become urgent needs. The rapid development of nanotechnology provides new solutions to this challenge, especially the application of nanoparticles in agriculture, which is gradually demonstrating its unique advantages and broad prospects. Nonetheless, various nanoparticles can influence plant growth in diverse manners, often through distinct mechanisms of action. Beyond their direct effects on the plant itself, they frequently alter the physicochemical properties of the soil and modulate the structure of microbial communities in the rhizosphere. This review focuses intently on the diverse methods through which nanoparticles can modulate plant growth, delving deeply into the interactions between nanoparticles and plants, as well as nanoparticles with soil and microbial communities. The aim is to offer a comprehensive reference for the utilization of functionalized nanoparticles in the agricultural sector.